THE RELATIONSHIP BETWEEN KNOWLEDGE AND THE READINESS OF COMMUNITY HEALTH NURSES IN EFFORT OF PREVENTION OF COVID 19 TRANSMISSION - Loren Juksen; Rafidaini Sazarni Ratiyun (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: The death of nurses due to exposed COVID–19 Virus is the problem all of the country around the world now. The effort to decrease the number of transmissions, death and exposed by the virus is cutting the chain of infection and transmission of the virus. Objectives: The study aims to know the relationship between knowledge and the Readiness of Community Health Nurses in Effort of Prevention of COVID–19 Transmission in Primary Health Center, Bengkulu City. Methods: The design of this study used survey analytics by cross-sectional approach. Samples were taken by purposive sampling techniques that were the community health nurses in Primary Health Center in Bengkulu City as many as 195 respondents. Research Instrument used the knowledge instrument and the readiness instrument and the data that were collected tested by Chi-Square Test. Results: From 110 respondents were good knowledge there were 76 persons (38.98%) were ready and 34 persons (17.43%) were not ready. From 59 respondents were fair there were 27 persons (13.85%) were ready and 32 persons (16.41%) were not ready. From 26 respondents were poor there were 10 persons 5.13% were ready and 16 persons 8.20% were not ready. The result from Chi-Square Test obtained that the value of person Chi-Square is 13.251 by P-Value 0.001< α 0.05, so the result H0 is rejected and Ha is accepted. Conclusion: The conclusion is there is significant relationship between Knowledge, and the Readiness of Community Health Nurses in Effort of Prevention of COVID–19 transmission in Primary Health Center, Bengkulu City.